2018
DOI: 10.1093/cid/ciy463
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Drug Resistance: 2018 Recommendations of the International Antiviral Society–USA Panel

Abstract: Testing for HIV drug resistance in drug-naive individuals and in patients in whom antiretroviral drugs are failing, and the appreciation of the role of testing, are crucial to the prevention and management of failure of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 106 publications
3
139
0
Order By: Relevance
“…86 For virologic failure of InSTI containing ART, integrase resistance testing is recommended (evidence rating AIII). 1,8789 Once a new regimen is started, HIV RNA level should be checked 4 to 6 weeks after initiation, following the same schedule as for monitoring of initial therapy (evidence rating AIII). 1 …”
Section: Laboratory Monitoringmentioning
confidence: 99%
“…86 For virologic failure of InSTI containing ART, integrase resistance testing is recommended (evidence rating AIII). 1,8789 Once a new regimen is started, HIV RNA level should be checked 4 to 6 weeks after initiation, following the same schedule as for monitoring of initial therapy (evidence rating AIII). 1 …”
Section: Laboratory Monitoringmentioning
confidence: 99%
“…All subjects received first-line ART regimen according to Chinese guidelines for diagnosis and treatment of HIV/AIDS [26]. This included two nucleoside reverse transcriptase inhibitors (NRTIs) and a non-nucleoside reverse transcriptase inhibitor (NNRTI) that are widely used globally [27][28][29][30][31]. All participants were followed up every 3 to 6 months for evaluation of VL, CD4 + T cell counts, and other routine clinical parameters.…”
Section: Study Populationmentioning
confidence: 99%
“…Numerous previous studies have demonstrated NGS methods detect more resistance-associated mutations at low frequencies that Sanger is unable to detect (11-20). However, the predictive value of detectable low frequency mutations for virological failure or other clinical outcomes remains unclear (21-23).…”
Section: Introductionmentioning
confidence: 99%